Aorto-enteric Fistula After Endovascular Abdominal Aortic Aneurysm Repair for Behcet's Disease Patient: A Case Report - Arworn, Supapong (EJVES Short Rep, 2018)
INTRODUCTION: A 42 year old male with Behcet's disease (BD) had endovascular treatment of a symptomatic infrarenal abdominal aortic aneurysm (AAA). Thirteen months later he developed haematemesis and melaena. METHODS: Computed tomography (CT) and angiography showed an aorto-enteric fistula with migration and kinking of the stent graft. Explantation of the infected graft and axillobifemoral bypass, aneurysm sac debridement, and jejunal repair with omental interposition was performed on this severely contaminated patient. DISCUSSION: There are no reports of an aorto-enteric fistula secondary to endovascular repair in the literature and this case describes the potential consequences of endovascular repair of AAA in BD. The aorto-enteric fistula was associated with persistent inflammatory aortitis, stent graft kinking, and infection. Five cases of secondary aorto-enteric fistulas following open AAA repair in BD patients have been reported including this case resulting from endovascular repair.